Մատենադարանի նորահայտ նկարազարդ մի էջ, որպես մշակութային ազդեցությունների խորհրդանիշ - Թաջարյան, Իվեթ; Էֆթեխարյան, Սարա Լափորթ (Մատենադարան)
In 2018, Sarah Laport-Eftekharyan donated a printed illustrated page entitled "The Beautiful Story of the People of Asia and the Caucasus" to Matenadaran. It belonged to the family of the donor's father, Pierre-Poghos Lazaryan for many years. The authors tried to find out as much as possible and to present the story of the picture. Since the work is based on an engraving, the authors write about the engraving technique, which helps to analyze the illustrated page that has not been studied so far. The thematic and stylistic features of the painting are related to the time of Hovnatanyans and the Qajars, but it was painted in Europe. The article examines the period of creation of the painting, the environment, the painting technique, the composition, the subject matter, the nationality of the represented persons, the position of each figure, their clothes, etc. The painter is Henri Félix Emmanuel Philippoteaux from France. The engraver is the Frenchman Pierre-Edouard Frère. Later it was water-colored and published in France in 1860. It was intended to be part of the book Foreigners in Paris but for an unknown reason was not included in it. After a scrupulous study, this page kept in Matenadaran can be regarded as a symbol of cultural interrelations. В 2018 году Сара Лапорт-Эфтехарян подарила Матенадарану печатную иллюстрированную страницу под названием “Прекрасная история народа Азии и Кавказа”, которая долгие годы принадлежала семье ее отца, Пьера-Погоса Лазаряна. Авторы попытались по возможности проследить историю этой работы. Поскольку статья посвящена гравюре, авторы обратились к технике гравировки, что помогло проанализировать ныне не изученную иллюстрированную страницу. Тематически и стилистически гравюра связана с временами Овнатаняна и Каджаров, но создана была в Европе. В статье описывается период создания картины, изучается окружение, техника письма, композиция, тема, национальность изображаемых лиц, положение каждой фигуры, их одежда и т. д. Автор работы – Анри Феликс Эмануэль Филиппо из Франции, гравер – француз Пьер Эдуар Фрер. Гравюра была раскрашена акварелью в 1860 г. и издана во Франции. Она была специально написана для книги «Иностранцы в Париже», однако по неизвестной причине не вошла в нее. Страница, хранящаяся в Матенадаране, может рассматриваться как свидетельство культурных влияний.
Keywords: Արվեստ